Tests to evaluate the physiological potential of Mombasa grass seeds - Carlos Bezerra Pereira, Francisco Elder [UNESP]; Martins, Cibele Chalita [UNESP]; Jeromini, Tatiane Sanches [UNESP]; Gomes-Junior, Francisco Guilhien; Torres, Salvador Barros (Univ Federal Ceara, Dept Geol, 2020)
Identifying fast and efficient tests to evaluate the vigor of forage grass seed lots is desirable in the quality control programs of the companies in this sector. Thus, the objective was to evaluate the efficiency of vigor tests on the physiological quality of seeds of Panicum maximum, cv. Mombasa, for the differentiation of lots and prediction of seedling emergence in the field. Nineteen seed lots were subjected to evaluations of moisture content, germination, first count, germination speed index, seedling emergence in sand, first count of seedling emergence in sand, seedling root and shoot lengths, seedling emergence in the field and computerized analysis of seedling images obtained through SVIS (R) software. The experimental design was completely randomized for the tests performed in the laboratory and randomized blocks for the emergence test in the field. The data were subjected to analysis of variance and the means were compared by Scott-Knott test at 5% probability level. Cluster analysis of seed lots and principal component analysis were performed. The uniformity index, evaluated by image analysis and by the root length test, is efficient in evaluating the physiological potential of seeds of Panicum maximum, cv. Mombasa, providing information similar to those obtained with the test of seedling emergence in the field.
Keywords: Panicum maximum; SVIS (R); Principal component; Vigor; Image analysis